Implementation and Evaluation of Gradient Strip Antimicrobial Susceptibility Testing in US Public Health Laboratories to Respond to Resistant Gonorrhea. Issue 12 (December 2021) - Raphael, Brian H.; Pham, Cau D.; Sharpe, Samera; Mauk, Kerry; Harvey, Alesia; Khubbar, Manjeet; Triplett, Laura; Soge, Olusegun O.; Denny, Michael; Palavecino, Elizabeth L.; Finney, Rose; Olsen, Aaron; et al.
Abstract : Background: Gradient strip antimicrobial susceptibility testing using Etest is conducted by local public health jurisdictions participating in the Strengthening the US Response to Resistant Gonorrhea (SURRG) program to inform public health responses to resistant gonorrhea. Proficiency testing results across the participating laboratories were analyzed and a comparison of Etest with the agar dilution method was conducted. Methods: Laboratories participating in SURRG performed Etest for azithromycin (AZM), cefixime (CFX), and ceftriaxone (CRO). Concurrence between minimum inhibitory concentrations (MICs) obtained with Etest versus the agar dilution method using corresponding isolates was defined as ±1 double dilution. Specific levels of reduced susceptibility were termed "alerts" and included isolates with the following MICs: ≥2.0 μg/mL (AZM), ≥0.25 μg/mL (CFX), and ≥0.125 μg/mL (CRO). Categorical (alert/nonalert) agreement was calculated for MICs determined using Etest and agar dilution methods. Results: Strengthening the US Response to Resistant Gonorrhea laboratories had high proficiency testing scores (≥98%) and low levels of interlaboratory variations in MICs. The overall concurrence of MICs (essential agreement) determined using agar dilution, and Etest was 96% (CRO), 96% (CFX), and 95% (AZM). Depending on the antibiotic tested, between 27% and 66% of isolates with alert MICs determined by Etest also had alert MICs using the reference agar dilution methodology; however, most of these alert MICs were detected at threshold levels. Conclusions: This study demonstrates that MICs produced by SURRG laboratories using Etest have a high level of concurrence with agar dilution. Although confirmation of specific alert MICs varied, Etest facilities rapid detection and response to emerging resistant gonorrhea. Abstract : Etest demonstrated a high level of reproducibility across laboratories. Concurrence of minimal inhibitory concentrations for azithromycin, cefixime, and ceftriaxone using agar dilution and Etest methods was 95% or greater.